Editorial - Romero Archila, Yuranny Marcela (Universidad Pedagógica y Tecnológica de Colombia, 2018)
ENLETAWA JOURNAL seeks to disseminate different experiences that have emerged from a diversity of teaching and learning contexts. Publishing is an outstanding opportunity to share knowledge and communicate one’s own experiences and thoughts to others, and ENLETAWA JOURNAL provides that space for first-time authors, as well as experienced ones. In this issue, we are pleased to present five papers that primarily deal with cultural identity, identity construction, feedback, Mobile Assisted Language Learning (MALL), and Student-Centered Learning (SCL).